2009 Systems and Information Engineering Design Symposium 2009
DOI: 10.1109/sieds.2009.5166167
|View full text |Cite
|
Sign up to set email alerts
|

Designing an automated water quality monitoring system for West and Rhode Rivers

Abstract: The Chesapeake Bay is the largest estuary in the United States, where its watershed is home to more than 3,600 species of plants and animals and more than 16.6 million people. However one of its major issues is water pollution. Good water quality is vital for the health of all these plants, animals and people. In order to act upon this problem and restore the water, there is the need to monitor the water quality. There are currently several organizations and agencies monitoring different parts of the bay and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In small study areas or small rivers, a low frequency approach is not a suitable approach since discharges and atmospheric events cause more sudden changes in water quality. In literature, continuous high frequency monitoring strategies are suggested for small study areas, without providing statistical explanation to the chosen monitoring frequency (Anvari et al, 2009;Chen and Han, 2018).…”
Section: Approaches To Selection Of Sampling Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…In small study areas or small rivers, a low frequency approach is not a suitable approach since discharges and atmospheric events cause more sudden changes in water quality. In literature, continuous high frequency monitoring strategies are suggested for small study areas, without providing statistical explanation to the chosen monitoring frequency (Anvari et al, 2009;Chen and Han, 2018).…”
Section: Approaches To Selection Of Sampling Frequencymentioning
confidence: 99%
“…Further, these networks need to be set up in advance, and have limited flexibility in terms of responding to unexpected events at different locations. Naddeo et al (2007) and Liu et al (2013) used statistical techniques to optimise low frequency (monthly or daily) datasets, and only two studies have been identified that deal with high frequency datasets (Anvari et al, 2009;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This new constraint on the development and densification of monitoring networks is in addition to the classically proposed pragmatic criteria such as the (i) existence of pollution sources and variability in water quality between the existing monitoring stations, (ii) infrastructure for ease of accessibility to the station, and (iii) the location of tributaries to the system (Chilundo et al, 2008;Anvari et al, 2009) and less frequently the spatial variability of processes (Polus et al, 2010). Meanwhile, Strobl et al (2006) have considered the information on land use such as point and non-point outflow sources and the watershed soil characteristics, hydrology, and topography in order to select the monitoring points; generally, there is no correlation between the size and the number of monitoring stations (Nguyen et al, 2019).…”
Section: How To Densify the Urban Monitoring Network?mentioning
confidence: 99%
“…STORET Legacy is more difficult to parse, though the EPA plans to incorporate it eventually into the Water Quality Portal. Remote sensing (satellite) measures of water color and clarity are also becoming more common (Lee, Orne, and Schaeffer 2014), as are automatic water quality monitors that can frequently detect and automatically report ambient levels (Anvari et al 2009). While remote sensing is becoming influential in air pollution research, its use in water pollution research in economics is nascent.…”
Section: Why a Dearth Of Economic Research On Water Pollution?mentioning
confidence: 99%